Antioxidant activity, α-Glucosidase inhibition and UHPLC–ESI–MS/MS profile of Shmar (Arbutus pavarii Pamp) - Buzgaia, Nawal; Lee, Soo Yee; Rukayadi, Yaya; Abas, Faridah; Shaari, Khozirah (Multidisciplinary Digital Publishing Institute, 2021)
The genus Arbutus (Ericaceae) has been traditionally used in folk medicine due to its phytomedicinal properties, especially Arbutus pavarii Pamp. However, this plant has not been evaluated for its efficacy, quality, and consistency to support the traditional uses, potentially in treating diabetes. Despite previous studies that revealed the biological activities of A. pavarii as antioxidant and α-glucosidase inhibitory agents, scientific reports on the bioactive compounds that contribute to its health benefits are still scarce. Therefore, this research focused on the evaluation of antioxidant and α-glucosidase inhibitory activities of the methanol crude extracts and various fractions of the leaf and stem bark, as well as on metabolite profiling of the methanol crude extracts. The extracts and fractions were evaluated for total phenolic (TPC) and total flavonoid (TFC) contents, as well as the DPPH free radical scavenging, ferric reducing antioxidant power (FRAP), and α-glucosidase inhibitory activities. Methanol crude extracts of the leaf and stem bark were then subjected to UHPLC–ESI–MS/MS. To the best of our knowledge, the comparative evaluation of the antioxidant and α-glucosidase inhibitory activities of the leaf and stem bark of A. pavarii, as well as of the respective solvent fractions, is reported herein for the first time. Out of these extracts, the methanolic crude extracts and polar fractions (ethyl acetate and butanol fractions) showed significant bioactivities. The DPPH free radical and α-glucosidase inhibitions was highest in the leaf ethyl acetate fraction, with IC50 of 6.39 and 4.93 µg/mL, respectively, while the leaf methanol crude extract and butanol fraction exhibited the highest FRAP with 82.95 and 82.17 mmol Fe (II)/g extract. The UHPLC–ESI–MS/MS analysis resulted in the putative identification of a total of 76 compounds from the leaf and stem bark, comprising a large proportion of plant phenolics (flavonoids and phenolic acids), terpenoids, and fatty acid derivatives. Results from the present study showed that the different parts of A. pavarii had potent antioxidant and α-glucosidase inhibitory activities, which could potentially prevent oxidative damage or diabetes-related problems. These findings may strengthen the traditional claim on the medicinal value of A. pavarii.